METHODOLOGY OF INTEGRATED ACCOUNTING AND CONTROL - TATYANA Serebryakova (Учёт. Анализ. Аудит, 2019)
The issues of integration of all types of accounting are not really new, they were formulated both theoretically and practically more than about 30 years ago when the automated systems of processing economic indicators, including the information from primary accounting documents, evolved. Nowadays they are becoming increasingly topical first due to the development of information technologies and second because a demand naturally arose for the standardization of accounting processes under conditions of consolidation and globalization of the economy. The article considers the possibility and necessity of introducing such new categories as “integrated accounting” and “integrated control”, and their relation to other types of accounting and control.